Pityriasis Rubra Pilaris In The Indian Scenario - Sarkar Rashmi; Bhalla Mala; Kaur Charandeep; Kanwar A.J (Wolters Kluwer Medknow Publications, 2002)
Pityriasis rubra pilaris (PRP) is an uncommon idiopathic papulosqamous disorder characterized by circumscribed follicular keratosis, palmoplantar keratoderma and frequently erythroderma. Seven patients of PRP (five females and two males) in the age range of 2 to 50 years seen over a 2-year period are presented with their clinical features, triggering factors, associations and laboratory investigations. The clinical type of PRP was adult onset classical variety in three, juvenile circumscribed variety in two and adult onset atypical variety and juvenile classical variety in one each. The triggering factors were upper respiratory tract infection with nutritional deficiencies in two and folliculitis in one. The histopathology was consistent with PRP in all. Four patients were managed with oral vitamin A while one each was put on methotrexate, etretinate and topical steroids and they showed a good response. More number of cases should be studied over a longer period to substantiate the suggested immunologic mechanism of PRP.